Tubular epithelial cell-derived extracellular vesicles carrying serum amyloid A1 exacerbate sepsis-associated acute kidney injury by promoting NETs formation - Jiao, Yang; Liu, Mei; Xie, Xin; Pi, Mengying; Zhou, Luyang; Zhu, Wei; Song, Jia; Zhang, Ti; Ma, Zhengliang; Gu, Xiaoping (Frontiers in Immunology, 2025)
IntroductionSepsis-associated acute kidney injury (SA-AKI) is a highly lethal condition with a rapid onset, and effective treatments are lacking because the molecular pathogenesis remains unclear. Tubular epithelial cells (TECs) have increasingly been recognized as driving forces in the progression of kidney diseases, partly through the release of extracellular vesicles (EVs) carrying proinflammatory cargos. However, the role of TEC-derived EVs on neutrophil extracellular traps (NETs) formation, which is an established feature of sepsis, and SA-AKI remains unclear.MethodsEVs isolated from phosphate buffer saline (PBS)/lipopolysaccharide (LPS)-treated TECs were injected intravenously into C57BL/6J wild type mice to determine whether TECs-derived EVs can directly induce NETs formation and kidney injury. Proteomics and single-cell RNA sequencing analysis were used to screen the key molecules that mediate the effects of TECs-derived EVs. EVs secretion from TECs and serum amyloid A1 (SAA1) expression in TECs were specifically inhibited via adeno-associated virus (AAVs). Finally, the association between SAA1 level in plasma EVs and clinical features of septic patients was determined.ResultsThis study demonstrated that EVs secreted from LPS-stimulated TECs exacerbated AKI by promoting NETs formation. Specifically blocking EVs secretion from TECs via AAVs reduced NETs formation and alleviated LPS-induced AKI. Bioinformatics analysis suggested that LPS increased SAA1 expression in TECs, and then released extracellularly through EVs. Further mechanistic studies revealed that SAA1 packaged in TECs-derived EVs was responsible for NETs formation and AKI via activation of the TLR4/p38 MAPK signaling pathway in neutrophils. Specifically inhibiting SAA1 upregulation in TECs via AAVs also reduced NETs formation and alleviated LPS-induced AKI. Interestingly, modulating EVs release from TECs or SAA1 expression in TECs also alleviated remote lung injury induced by LPS, indicated that TECs-derived EVs may participate in kidney‒lung crosstalk during sepsis. Furthermore, plasma TECs-derived EVs proportion and SAA1 expression in plasma EVs may be promising prognostic indexes for SA-AKI patients.DiscussionHere, we explored a new mode of TECs-neutrophils crosstalk mediated by EVs during SA-AKI, and strategies to modify TECs-derived EVs and the cargo SAA1 could be a new avenue for developing therapeutics against SA-AKI.